Report Of The Asian Multicity Epidemiology Workgroup 1999. - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1999)

(untitled)
The Asian Multi-City Epidemiology Study Program has entered its seventh year in 1999. The Asian Multicity Epidemiology Work Group (AMCEWG), now consisting of 23 cities has been established. A city based surveillance system has been developed in twelve cities.